Standards of Proof in Ukrainian Procedural Law: Sectoral Conditionality and New Features - Vasyliev, Sergii (Problems of legality, 2025)
In the context of bringing Ukrainian legislation closer to European standards and unifying legal terminology, it is appropriate to use the term “standard of proof” as a procedural guideline that the court should follow when deciding a case. Thanks to such standards, the court is able to assess how effectively the parties have fulfilled their burden of proof and whether they have been able to convince the court of the correctness of their arguments. Taking into account the works of domestic and foreign scholars, analysis of legislation and established judicial practice, the system and content of standards of proof in civil, administrative and criminal proceedings have been analyzed. This assessment of the peculiarities of the functioning of standards of proof in the practice of the European Court of Human Rights serves as a benchmark for procedural law in terms of the application of certain standards of proof in various legal spheres. It is proposed to use the following basic types of standards of proof in national procedural law: “balance of probabilities” or “preponderance of the evidence” “beyond reasonable doubt” and “clear and convincing evidence” the rules and cases of use of which should be useful in the administration of justice. It has been established that the characteristic features of the relevant types of judicial proceedings determine the peculiarities of the application of certain standards of proof. It has been established that each of the standards of proof has its own content, which, on the one hand, provides for the presence of a set of relevant, admissible, and reliable evidence, and on the other hand, determines the level of probability of establishing the circumstances relating to the disputed legal relations; it is this level of knowledge that is a necessary prerequisite for making a well-founded procedural decision. It is emphasized that the distinction between basic and additional standards of procedural evidence is a very important element of domestic judicial proceedings, as it will contribute to the development of a uniform approach to procedural decisions and procedural actions by all subjects of evidence in various types of court proceedings, which improves the effectiveness of evidentiary activities.